In silico phytochemicals analysis as inhibitors of the SARS-COV-2 main protease - Ekaterina Serikova; Victor Gustavo Oliveira Evangelho; Marianna Kremenevskaya; Camila Ferreira Mattos; Juliana Silva Novais; Marcos Vinicius Santana; Carlos Rangel Rodrigues; Reinaldo Barros Geraldo; Helena Carla Castro (International Journal of Pharmaceutical Sciences and Developmental Research - Peertechz Publications, 2022)
Background: The world population's full immunization with vaccines against SARS-CoV-2 is still challenging. Therefore, more research must be needed to find an active antiviral drug against the virus, including new mutated strains. Results: Therefore, this research analyzes 35 natural compounds isolated from various plants against SARS-CoV-2 main protease (Mpro) using an in silico strategy. According to the results, it was possible to identify promising molecules using a molecular docking strategy. Furthermore, the results showed that the interaction of these molecules with protease-specific residues, including (2S)-Eriodictyol 7-O-(6''-O-galloyl)-beta-D-glucopyranoside (Trp207, Ser284, and Glu288), Hypericin (Glu166, Arg188, and Thr190), Calceolarioside B (Gly143, Ser144, Cys145, Glu166, Arg188, and Gln192), Epicatechin (Ser144, His163, and Leu167) and Myricitrin (Thr190) with ΔG was -8.5, -9.6, -8.5, -9.3 and -9.3 kcal/mol, respectively. In addition, analyzing all compounds for their ADME properties shows that compounds present an excellent pharmacokinetic profile.  Conclusion: In conclusion, the results of this study indicated that these major natural compounds can be considered potential inhibitors of Mpro and should be further explored in vitro and in vivo in accordance with our data.